2021
DOI: 10.21083/ajote.v10i1.6287
|View full text |Cite
|
Sign up to set email alerts
|

Students’ Perspectives on Satisfaction with Distance Education in Ghana: A Cluster Analysis

Abstract: This study sought to categorise students based on the preferences that influenced their choice of distance education program in Ghana.  Questionnaires were used to collect data from 120 students taking part in the University of Education, Winneba (UEW) distance education (DE) programme at the Kumasi Girls Senior High School [SHS] Study Center. Respondents were segmented into three clusters (highly, moderately, and least satisfied) based on four preferences (price, quality, packaging, and social boding) that in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…In their study investigating the social dimensions of distance education in high schools, Lidegran et al (2021) identified three clusters: urban upper-middle-class, immigrant working-class, and rural working-class. Agyapong (2021) divided students into three clusters, which were highly, moderately, and least satisfied based on preferences (price, quality, packaging, and social bonding) that influenced their distance education program choices. Students in the highly satisfied cluster were driven by the education program's service quality and competitive fee structure.…”
Section: Innoeduca International Journal Of Technology and Educationa...mentioning
confidence: 99%
“…In their study investigating the social dimensions of distance education in high schools, Lidegran et al (2021) identified three clusters: urban upper-middle-class, immigrant working-class, and rural working-class. Agyapong (2021) divided students into three clusters, which were highly, moderately, and least satisfied based on preferences (price, quality, packaging, and social bonding) that influenced their distance education program choices. Students in the highly satisfied cluster were driven by the education program's service quality and competitive fee structure.…”
Section: Innoeduca International Journal Of Technology and Educationa...mentioning
confidence: 99%
“…Their possessing different characteristics necessitates the need for segmenting them into groups so that while evaluating their perception regarding a certain issue, their needs can be understood and proper corrective action can be taken. Thus, it has been used by different scholars in distance education to analyse distance learners (Saxena et al, 2004), to explore the factors of their satisfaction with a distance education course (Agyapong, 2021;Ozyurt, 2014) to determine their dropout rate etc. (Desjardins et al, 2021).…”
Section: Cluster Analysismentioning
confidence: 99%